2013
DOI: 10.1182/blood-2012-11-468264
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin expands regulatory T cells via induction of cyclooxygenase-2–dependent prostaglandin E2 in human dendritic cells

Abstract: production, and Treg expansion were mediated in part via interaction of IVIg and F(ab9) 2 fragments of IVIg with DC-specific intercellular adhesion molecule-3-grabbing nonintegrin. Our results thus uncover novel cellular and molecular mechanism by which IVIg expands Tregs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
114
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 49 publications
6
114
0
3
Order By: Relevance
“…Thus, these results corroborate our previous data indicating a role for DC-secreted PGE 2 in IVIg-mediated Treg expansion and, hence, validate the therapeutic relevance of our report. 8 Notably, the up-regulation of PGE 2 was also minimal in a patient who did not show Treg enhancement (Figure 1b). Therefore, these results indicate that Treg expansion by IVIg is directly linked to the amount of absolute increase in PGE 2 .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, these results corroborate our previous data indicating a role for DC-secreted PGE 2 in IVIg-mediated Treg expansion and, hence, validate the therapeutic relevance of our report. 8 Notably, the up-regulation of PGE 2 was also minimal in a patient who did not show Treg enhancement (Figure 1b). Therefore, these results indicate that Treg expansion by IVIg is directly linked to the amount of absolute increase in PGE 2 .…”
mentioning
confidence: 99%
“…6,7 Recently, we demonstrated that IVIg-mediated Treg expansion requires the induction COX-2-dependent PGE 2 in human DCs. 8 The inhibition of COX-2 activity in DCs led to the abrogation of IVIg-mediated Treg expansion both in vitro and in vivo in an experimental autoimmune encephalomyelitis model. However, the effect of IVIg therapy on PGE 2 levels in autoimmune patients has not yet been investigated.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[11] This expansion maybe partly via induction of cyclooxygenase (COX)-2-dependent prostaglandin E2 in antigenpresenting cells (APCs). [12] On the other hand, recent studies demonstrate that, regardless of the brand or the product batch, all IVIg preparations studied were found to equally inhibit the production of IL-17A from Th17 cells in vitro. [13] These observations suggest that the anti-inflammatory effect of IVIg helps to restore immune tolerance in autoimmune and inflammatory conditions.…”
mentioning
confidence: 99%